Malaysia : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This Selected Issues paper analyzes the use of capital controls and evolution of the capital control regime in Malaysia. The paper highlights that following a period of strong downward pressures on the ringgit, the Malaysian authorities introduced on September 1, 1998 a wide range of capital controls along with pegging the exchange rate at RM 3.8 vis-a-vis the U.S. dollar. The paper provides a brief review of Malaysia's approach to capital account liberalization prior to September 1998. It also reviews the circumstances surrounding the imposition of the controls in September 1998, and their impact.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet